BIBLOS Vol. 28, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
BIBLOS Vol. 28, n. 1 (2014) Link de acesso ao númerohttp://www.seer.furg.br/biblos/issue/view/446/showToc